Carta de Roy O. West a Roberto H. Todd - Todd, Roberto H.; West, Roy O. (My University, 1924)
Carta relacionada a aceptación de representantes por Puerto Rico en le Comité Nacional Republicano.
Keywords: Republican National Committee; Soto, John B.; Harrison, Johnson; Hilles, Charles D., 1867-1949